Sensitivity analysis of a single phase to ground fault system in connection with high impedance faults: A case study. Issue 1 (1st January 2020) - Velmurugan, Perumal; Chattopadhayay, Adhir Baran
Abstract: Most of High-impedance faults (HIFs) occur due to broken conductors falling on high-resistivity desert soil in United Arab Emirates remain undetected due to incredibly low fault currents and endanger lives. A reliable detection method is needed. A live line test conducted on a 11kV distribution line by switching to a remotely laid conductor did not result enough detectable fault currents. This motivated conducting a literature survey and researching for the reasons why the modern numerical protection relays could not detect such low current faults. Hence, a sensitivity analysis of a single-phase-to-ground system is carried out. Mathematical modelling for the sensitivity analysis is performed using differential calculus. Applying definition of sensitivity to a set of power system equations to analyze to provide guidance for detection of high impedance faults is entirely a new approach. This paper provides a comprehensive analysis of single phase to ground fault system by exhibiting profiles of fault currents, line, neutral, and MV bus voltages for a range of fault impedance. The sensitivity analysis results conclude that low-fault current signals should be collected from the neutral line of the distribution system instead of focusing on the line voltage, current, power and other parameters.